PENGARUH JENIS MEDIA TERHADAP KONSENTRASI BIOMASSA DAN KLOROFIL MIKROALGA Tetraselmis chuii - Wisnawa Putra, I Komang Rai; Dewi Anggreni, Anak Agung Made; Arnata, I Wayan (JURNAL REKAYASA DAN MANAJEMEN AGROINDUSTRI, 2015)
This study aims were to determine the effect of medium type on biomass of Tetraselmis chuii and to find out the best type of medium for producing biomass of Tetraselmis chuii. This study used a descriptive quantitative method with treatment of medium consisting of 3 medium types, namely Walne, Miquel-Allen (MQ), and Bold Basal Medium (BBM). Observation of cell biomass concentration Tetraselmis chuii was used haemacytometer with 3 replications. The results of this study showed that the medium type had significantly affect on the biomass concentration of Tetraselmis chuii. BBM was the best medium to produce the highest biomass of Tetraselmis chuii with a density 2.2 x 10 6 (cells/ml) on 10 days cultivation
Keywords: 41